2018
DOI: 10.1080/00221309.2017.1411682
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs about Memory as a Mediator of Relations between Metacognitive Beliefs and Actual Memory Performance

Abstract: The goal of the present study was to investigate relationships between personal beliefs about memory, metacognitive beliefs, and actual memory performance. One hundred thirty-seven participants' (aged 20 to 60 years) metacognitive beliefs were measured using the Metacognition Questionnaire (MCQ-30), memory beliefs were measured using the Personal Beliefs about Memory Instrument (PBMI), and an episodic memory task was used to measure actual memory performance, memory predictions, and postdictions. Younger adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 21 publications
2
14
0
Order By: Relevance
“…Consistent with previous results [1,9,44,45] although late middle-aged participants scored lower on the cognitive confidence subscale than younger and middle-aged changes in their memory also had higher (more negative) scores on MCQ-30 subscales. However, neither TAF-moral nor TAF-probability subscales were related to reliability of memory and retrospective changes in memory.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Consistent with previous results [1,9,44,45] although late middle-aged participants scored lower on the cognitive confidence subscale than younger and middle-aged changes in their memory also had higher (more negative) scores on MCQ-30 subscales. However, neither TAF-moral nor TAF-probability subscales were related to reliability of memory and retrospective changes in memory.…”
Section: Discussionsupporting
confidence: 91%
“…Our results have revealed a significant effect of age on aspects of memory beliefs, namely, about retrospective changes in memory and reliability of memory, with young adults showing more positive beliefs than middle-aged and late middle-aged individuals. Also, consistent with previous studies [2,44,47,48], the young adult group held more positive views about memory and reported less cognitive failure compared to the middle-aged and late middle-aged groups. Our results support the suggestion by Berger and Thompson [43] that holding negative beliefs about cognitive abilities and of middle-and old age implicitly and prejudicially affects cognitive performance.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Tajrishi, Mohammadkhani, & Jadidi, 2011 ), memory performance (e.g. Horhota et al, 2012 ; Irak & Çapan, 2018 ), social functioning (Bright et al 2018 ), spontaneous thinking (for a review see Morewedge & Kupor, 2018 ), and well-being (Sellers, Varese, Wells, Morrison, 2017 ; Østefjells et al, 2017 ), to name just a few.…”
Section: Introductionmentioning
confidence: 99%
“…Another possibility is that negative appraisals encourage poor PM behaviors, for example, if people with PTSD believe their memory is poor, they might stop effortfully encoding and recalling intentions—or bias how people report these behaviors—they might report consistent with their appraisals. We know that more generally, metamemory judgments (i.e., memory self-efficacy, metacognitive beliefs) are associated with retrospective and PM performance—for example, recalling word lists, pressing a target key every 2 min (e.g., Irak & Çapan, 2018; Kliegel & Jäger, 2006; see Beaudoin & Desrichard, 2011, for review)—and that people’s appraisals of their memory and cognitive abilities correlate with self-report PM (i.e., Swain & Takarangi, 2021). However, we know of no existing evidence that appraisals directly change PM behaviors .…”
mentioning
confidence: 99%